Analisa Nilai KAO dengan Metode Narrow Range pada Campuran Asphalt concrete – Wearing Course menggunakan Pasir Laut - Aqilah Attamimi; Imran Imran; Irfanti S. La Djail; Angjali Labika (Pusat riset dan Inovasi Nasional, 2022)
The use of sea sand in construction work from an economic point of view does have advantages. One of them is increasing the income of the sea sand collectors who are spread throughout the area in Fakfak Regency. In addition, the potential availability of sea sand is quite large and is able to accommodate all types of concrete construction work in this area. This study aims to determine and analyze the use of sea sand in the AC-WC mixture of course by doing the Marshall test. This study uses variations in asphalt content of 5.0%, 5.5%, 6.0%, 6.5% and 7.0%, this study was carried out using Marshall testing in accordance with the general specifications of Bina Marga 2018. The results of the research conducted showed a relationship asphalt content and Marshall parameters such as stability value, VMA, density, MQ at an asphalt content of 5.0%-7.0%, meet the specifications of 1932 kg, 19.84%, 2.26 gr/cm3 and 1031 kg/mm. Values of VIM, VFWA and flow at 5.5% asphalt content are known to not meet the mix spasticity, namely 8.07%, 59.71% and 1.67 mm. Based on the Marshall parameter data, the Optimum Asphalt Content value is 6.5%.